2021
DOI: 10.1001/jamanetworkopen.2021.21867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Electrocardiogram Monitoring on Detection of Undiagnosed Atrial Fibrillation After Hospitalization for Cardiac Surgery

Abstract: IMPORTANCE Postoperative atrial fibrillation (POAF) occurring after cardiac surgery is associated with adverse outcomes. Whether POAF persists beyond discharge is not well defined. OBJECTIVE To determine whether continuous cardiac rhythm monitoring enhances detection of POAF among cardiac surgical patients during the first 30 days after hospital discharge compared with usual care. DESIGN, SETTING, AND PARTICIPANTS This study is an investigator-initiated, open-label, multicenter, randomized clinical trial condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…A recent study using continuous monitoring found a POAF rate of 19.6% through 30 days after discharge. 7 While there is an association between POAF and late strokes, most observed strokes in ATLAS were perioperative. It cannot be assumed that the impact of LAAE on the stroke rate in patients with POAF is the same as the impact of LAAE on late strokes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using continuous monitoring found a POAF rate of 19.6% through 30 days after discharge. 7 While there is an association between POAF and late strokes, most observed strokes in ATLAS were perioperative. It cannot be assumed that the impact of LAAE on the stroke rate in patients with POAF is the same as the impact of LAAE on late strokes.…”
Section: Discussionmentioning
confidence: 99%
“…6 POAF, including asymptomatic, has been shown to continue out to at least 30 days. 7 The majority of in-hospital POAF is paroxysmal, and patients are in sinus rhythm at discharge. However, POAF is associated with a 5- to 8-fold increased risk of future development of AF.…”
Section: Introductionmentioning
confidence: 99%
“…In a validation study by Nault et al, the agreement between CardioSTAT and Holter monitor readings on AF detection was very high ( 53 ). In patients following cardiac surgery, a high-risk population for arrhythmic events, post-operative AF detection was increased by more than ten times, when individuals were continuously monitored with the CardioSTAT patch, compared to those assigned to usual care ( 75 ).…”
Section: Wearables For Detection Of Atrial Fibrillationmentioning
confidence: 99%
“…For instance, Ha et al demonstrated continuous patch-based cardiac monitoring improves detection of post-operative atrial fibrillation by 18%. 71 The trial consisted of 336 adults, average age of 67.5 years, predominantly male (78%), and predominantly white (>82%). In both control and treatment arms of the study, the median CHADS-VASc score was 4.0 and median HAS-BLED score 72 was 2.0.…”
Section: Introductionmentioning
confidence: 99%